ANALISIS DAYA SAING KEDELAI DI JAWA TIMUR - Muhammad Firdaus (University of Jember, 2007)
The objective of the study were (1) to know the trend of crop area, production and productivity of soybean in East Java; (2) to know competitiveness of soybean (e.g. comparative and competitive advantage) in East Java; (3) to determine and analyze the impact of government policy related to soybean competitiveness in East Java; and (4) to know the effect of changes in tradable input and output to soybean competitiveness in East Java. The determination of research area was based on purposive sampling method with the consideration that East Java Province is one of main soybean production center. The samples were determined by Multi Stage Cluster Sampling Method. The method of data analysis used in this study was trend analysis and Policy Analysis Matrix (PAM). The results of analysis indicate that (1) trend of crop area and production of soybean will gradually decrease, but its productivity will increase for the coming years; (2) Privately, soybean agribusiness in Jember and Banyuwangi were efficient. While socially, soybean agribusiness in Jember was efficient, but in Banyuwangi was inefficient; (3) Soybean agribusiness in Jember had comparative and competitive advantage, on the other hand soybean agribusiness in Banyuwangi had competitive advantage, but did not have comparative advantage; (4) The impact of government policy related to soybean competitiveness in East Java was positive; (5) Decreasing in tradable input price will increase the competitiveness of soybean agribusiness, while increasing in tradable input price will decrease the competitiveness soybean agribusiness in both region. The upper bound of increase in tradable input price was 102,21% for soybean agribusiness in Jember and 13,85% for soybean agribusiness in Banyuwangi, (6) Decreasing in soybean price will decrease the competitiveness of soybean agribusiness. The upper bound of decrease in output price was 11,13% for soybean agribusiness in Jember and 1,50% for soybean agribusiness in Banyuwangi, (7) Decreasing in productivity of soybean will decrease the competitiveness of soybean agribusiness. The upper bound of decrease in productivity was 11,13% for soybean agribusiness in Jember and 3,00% for soybean agribusiness in Banyuwangi. Keywords: soybean, trend, comparative and competitive advantage